FAKTOR YANG MEMPENGARUHI WAKTU KERJA PEREMPUAN DAN KESEJAHTERAAN KELUARGA PADA INDUSTRI KERAJINAN KAYU DESA MAS - Prabhajayati, Putu Srila Lohita; Marhaeni, A.A.I.N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021DO - 10.24843/EEB.2021.v10.i12.p09, 2021)
The purpose of this study was to analyze the effect of work experience, number of family dependents and husband's employment status on the allocation of women's working time in the wood craft industry in Mas Village; the effect of work experience, number of family dependents, husband's employment status and allocation of women's working time on family welfare in the wood craft industry in Mas Village; and the role of women's work time allocation in mediating the effect of work experience and number of family dependents and husband's employment status on family welfare in the wood craft industry in Mas Village. Data were obtained using observation and interview methods, with a total sample of 97 people which were then analyzed using path analysis. The results showed that work experience had a non-positive or non significant effect on the allocation of women's working time, while the number of family dependents had a positive and significant effect on the allocation of women's working time, and husbands who had employment status had a lower allocation of women's working time than husbands who did not work; Work experience, number of dependents in the family has no effect on family welfare, while husbands who have employment status work have higher family welfare than husbands who do not work, and the allocation of women's working time has a positive and significant effect on family welfare; Work experience, number of family dependents and husband's employment status indirectly affect family welfare through the allocation of women's working time, in other words, women's work time allocation is an intervening variable that mediates work experience, number of family dependents and husband's employment status on women's working time allocation. . Meanwhile, the husband's employment status has no direct effect on family welfare.